Language as a Bridge: The Influence of Mother Tongue on English Learning among Junior High School Students - Balonglong, Cynthia; Tugmoy, Clyde (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the influence of mother tongue use on English learning among junior high school students in Tadian, Mountain Province. Anchored on the view that the first language serves as a cognitive scaffold in second language acquisition and supported by translanguaging perspectives, the study investigated how strategic mother tongue use contributes to learners’ comprehension, classroom participation, confidence, and engagement. A quantitative descriptive correlational research design with regression analysis was employed. The respondents consisted of 21 junior high school students selected through stratified sampling with equal allocation. Data were collected using a researcher made questionnaire and analyzed using frequency counts, percentages, weighted mean, standard deviation, Pearson Product Moment Correlation Coefficient, and multiple regression analyses. The findings revealed a high extent of mother tongue use in English classes, particularly in explaining vocabulary and concepts, processing ideas in the first language, clarifying instructions, and facilitating classroom discussions. The respondents also demonstrated a high level of English learning, with engagement receiving the highest rating, followed by confidence, comprehension, and classroom participation. Descriptively, the findings indicated that strategic mother tongue use functioned as a cognitive and instructional bridge that supported English learning rather than replacing English as the medium of instruction. However, the intended correlation, regression, and moderation analyses could not be completed because the available data were aggregated rather than recorded at the respondent level, preventing the establishment of a statistically significant relationship or predictive influence between the variables. The study concludes that strategic mother tongue use can effectively support English learning when integrated appropriately into classroom instruction and recommends context sensitive language practices, supportive speaking activities, and future studies using larger samples and respondent level datasets. The study aligns with Sustainable Development Goal 4 (Quality Education) by promoting inclusive and equitable language instruction that recognizes learners’ linguistic backgrounds. Its findings contribute to educational, institutional, and community sustainability by supporting evidence based multilingual teaching practices and context responsive language policies.